Monarquía administrativa y ciencia de la policía - Sanchez Raygada, Carlos Hugo (Revista de Derecho, 2019)
Usually, historiography presents police as a precedent of Administrative Law. Nevertheless, a general overview explains the reason of reflection on the socio-political context preceding the liberal revolution. Administrative Law will appear with the suppression of the corporations and its jurisdictions in favor to a State concentration’s. Administrative monarchy arises during XVII Century with a new political approach, product of new financial theories, as mercantilism, which emphasize the kingdom power its set up by the wealth produced, and not only by the conquer of new territories. Trying to adapt society to the governor’s new economic concerns, a new authority speech is created connecting the medieval tradition of the king-judge with the new icon of the king as a father protecting his subjects. In such a context returns the old concept of police related with the policy, to refer a society’s control necessary to get prosperity and happiness